Relationship between the Pavement Condition Index (PCI), Present Serviceability Index (PSI), and Surface Distress Index on Soekarno Hatta Road, Bandung - Nur, Wahyudin; Subagio, Bambang Sugeng; Hariyadi, Eri Susanto (Jurnal Teknik Sipil, 2019)
Evaluation of the conditions of Jalan Soekarno Hatta using PCI method shows that the condition of "Good" both on rigid and flexible pavement is most common, with the percentage of each of them being 61.9% and 21.6%. Meanwhile, by using PSI method, the most commonly found are "Fair" conditions both in rigid and flexible pavement, with the percentage of each being 81% and 48,9%.  Using the SDI method on the flexible pavement, the most commonly found is the condition of "Medium" with a percentage of 65,9%. The parametric analysis between PCI and PSI on rigid pavement produced R2 = 0.0548 with a regression equation of PCI = 96,66 ? 3,9352 x PSI, while PCI and PSI correlation on flexible pavement produced R2 = 0.8163 with regression equation of PCI = 27,673 + 16,848 x PSI., and PCI and SDI correlations on flexible pavement yields R2 = 0,8653 with a regression equation of PCI = 94,663 ? 0,4462 x SDI The non-parametric analysis between PCI and PSI on rigid pavement produced a correlation coefficient of 0.043, while the PCI and PSI values on flexible pavements produced a correlation coefficient of 0.397, and PCI and SDI on flexible pavement produced a correlation coefficient of 0.492. Based on the two methods, both parametric and non parametric analysis, the relationship between PCI and SDI was considered better than the PCI and PSI relationship because it produced an R2 value and a greater correlation coefficient Evaluasi kondisi Jalan Soekarno Hatta dengan menggunakan metode PCI menunjukan bahwa yang paling banyak di temukan adalah kondisi ?Good? baik pada perkerasan kaku maupun perkerasan lentur, dengan persentase masing masing adalah 61,9 % dan 21,6 %. Sedangkan dengan menggunakan metode PSI yang paling banyak di temukan adalah kondisi ?Fair? baik pada perkerasan kaku maupun perkerasan lentur, dengan persentase masingmasing adalah 81 % dan 48,9 %. Dengan menggunakan metode SDI pada perkerasan lentur yang paling sering di temukan adalah kondisi ?Sedang? dengan persentase 65,9 %. Analisis parametrik antara PCI dan PSI pada perkerasan kaku menghasilkan nilai R2= 0,0548 dengan persamaan regresi yaitu PCI= 96,66 ? 3,9352 x PSI, sedangkan korelasi PCI dan PSI pada perkerasan lentur menghasilkan nilai R2= 0,8163 dengan persamaan regresi yaitu PCI = 27,673 + 16,848 x PSI, dan korelasi PCI dan SDI pada perkerasan lentur menghasilkan nilai R2= 0,8653 dengan persamaan regresi yaitu PCI = 94,663 ? 0,4462 x SDI. Analisis non parametrik antara PCI dan PSI pada perkerasan kaku menghasilkan nilai koefisien korelasi sebesar 0,043, sedangkan nilai PCI dan PSI pada perkerasan lentur menghasilkan nilai koefisien korelasi sebesar 0,397, dan nilai PCI dan SDI pada perkerasan lentur menghasilkan nilai koefisien korelasi sebesar 0,492. Berdasarkan kedua metode analisis baik analisis parametrik maupun non parametrik hubungan PCI dan SDI dinilai lebih baik dibandingkan hubungan PCI dan PSI karena menghasilkan nilai R2 dan koefisien korelasi yang lebih besar.